Antioxidant profile of tomato landraces for fresh consumption - Csambalik, László; Orbán, Csaba; Stéger-Máté, Mónika; Pusztai, Péter; Divéky-Ertsey, Anna (Acta Biologica Szegediensis, 2016)
Tomato is one of the most important and frequently consumed vegetable species in Hungary, as well as a significant vitamin source throughout the year. Due to its antioxidant content, tomato consumption is related to the reduced occurrence of cardiovascular diseases and certain cancer types. In our study, four Hungarian tomato accessions [RCAT030275 (Cegléd), RCAT031012 (Veresegyház), RCAT031095 (Cigánd), RCAT054422 (Jánoshalma)] and a commercial cultivar (Hellfrucht) were investigated according to antioxidant capacity [ferric reducing power (FRAP), total phenol content (TPC) and radical scavenging activity (DPPH)], lycopene and ascorbic acid content. A two year (2013-2014) open field trial was carried out in the certified organic area of SZIE Soroksár Experimental and Educational Station. Our results showed that no significant differences were between the landraces and the variety in DPPH values, while TPC values were higher in both years in the landraces, especially in RCAT031095, and RCAT054422. The lycopene content of RCAT031012, RCAT031095 and RCAT054422 was also higher in both years than those of Hellfrucht. The results demonstrate that small-scale production of the investigated landraces could be marketable.